The river ebook A novel. - Heller, Peter (2019)
NATIONAL BESTSELLER • From the author of The Guide and The Dog Stars comes the story of two college students on a wilderness canoe trip—a gripping tale of a friendship tested by fire, white water, and violence. "A fiery tour de force … I could not put this book down. It truly was terrifying and unutterably beautiful."— The Denver Post Wynn and Jack have been best friends since college orientation, bonded by their shared love of mountains, books, and fishing. Wynn is a gentle giant, a Vermont kid never happier than when his feet are in the water. Jack is more rugged, raised on a ranch in Colorado where sleeping under the stars and cooking on a fire came as naturally to him as breathing. When they decide to canoe the Maskwa River in northern Canada, they anticipate long days of leisurely paddling and picking blueberries, and nights of stargazing and reading paperback Westerns. But a wildfire making its way across the forest adds unexpected urgency to the journey. One night, with the fire advancing, they hear a man and woman arguing on the fog-shrouded riverbank; the next day, a man appears on the river, paddling alone. Is this the same man they heard? And if he is, where is the woman? From this charged beginning, master storyteller Peter Heller unspools a headlong, heart-pounding story of desperate wilderness survival.